Muscle activation patterns correlate with race walking economy in elite race walkers: A waveform analysis - Gomez-Ezeiza, J.; Santos-Concejero, J.; Torres-Unda, J.; Hanley, B.; Tam, N.Pages (International Journal of Sports Physiology and Performance, 2019)
Purpose: To analyze the association between muscle activation patterns on oxygen cost of transport in elite race walkers over the entire gait waveform. Methods: A total of 21 Olympic race walkers performed overground walking trials at 14 km·h/1 where muscle activity of the gluteus maximus, adductor magnus, rectus femoris, biceps femoris, medial gastrocnemius, and tibialis anterior were recorded. Race walking economy was determined by performing an incremental treadmill test ending at 14 km·h-1. Results: This study found that more-economical race walkers exhibit greater gluteus maximus (P = .022, r = .716), biceps femoris (P = .011, r = .801), and medial gastrocnemius (P = .041, r = .662) activation prior to initial contact and weight acceptance. In addition, during the propulsive and the early swing phase, race walkers with higher activation of the rectus femoris (P = .021, r = .798) exhibited better race walking economy. Conclusions: This study suggests that the neuromuscular system is optimally coordinated through varying muscle activation to reduce the metabolic demand of race walking. These findings highlight the importance of proximal posterior muscle activation during initial contact and hip-flexor activation during early swing phase, which are associated with efficient energy transfer. Practically, race walking coaches may find this information useful in the development of specific training strategies on technique.